Boundary continuity effects on development of membrane actions for composite beam-slab sub-assemblages at elevated temperature - Liu, Junxian (2016)
Composite beam-slab systems have been widely used in the modern building construction as they not only reduce the constructional cost, but also expedite construction schedule compared to traditional reinforced concrete slab systems. However, steel profiled decking and supporting steel beams are vulnerable under fire condition. It is necessary to provide sufficient fire protection materials to keep these components under certain temperature for a period of time. Fire protection is costly and sometimes not necessary. Through several large-scale fire tests conducted in Europe, despite of unprotected interior supporting steel beams, it is observed that composite beam-slab systems have a superior fire performance due to mobilisation of tensile membrane action. Therefore, the British Research Establishment (BRE) published SCI-P288 and SCI-P390 design guidelines for steel framed composite slabs by taking account of tensile membrane action at fire limit state. Since these two design guidelines were only validated through limited fire tests and focused on isolated composite slab panels, the proposed work seeks to examine these guides more deeply, especially with regard to deflection limit validation and continuity effects on the development of tensile membrane action. Three series of nine specimens with one-quarter scale composite slabs were fabricated and tested at elevated temperature in Nanyang Technological University. The main investigated parameters included structural continuity effect and aspect ratios (1 and 1.5). Compared with SCI-P288 and SCI-P390, the test results showed that this design method was conservative. Even at the defined deflection limits in the SCI-P288 and SCI-P390, there were still reserves for the load-bearing capacity of these specimens. To find out the development of membrane actions, numerical models were built up by ABAQUS. From the analyses, both compressive and tensile membrane forces were developed and the equilibrium was achieved by forming a tensile membrane zone in the middle surrounded by a peripheral compressive ring. Based on membrane forces distribution from the numerical analyses, a revised analytical model was proposed by incorporating the boundary restraint forces. Compared with the test results, the author's analytical model showed good predictions of the load-bearing capacity for composite slabs at the fire limit state by incorporating edge beams forces.